What are some clever ploys psychotherapists use to avoid knowing their own "foundational beliefs"? - R. Mahrer, Alvin (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF